Mulheres, trabalho e dendeicultura na amazônia: transformações e desafios em Tailândia – PA - PONTES, Lana Glayce Dias Ferreira (Universidade Federal do Pará, 2020)
The present article aims to understand the transformations of female labour on the farms and how it is related with the local environment proposal which reinforce: how those transformations of female labour on the farms are processed considering the breakthrough made in Elaeis guineenses monoculture? This research is an integral part of the studies which has been realized by the research group named GAAGPAM/NUMA/FPA about this monoculture in Pará State. That thought seek to identify the female profile of the women who works on the network of palm oil and their education, relating these women to the rural association overall and their decision-making. Therefore, this discussion focuses on the theoretical, more specifically in three categories: Female Labour, Dendê monoculture and Local Development, by the approach of Vandana Shiva and Regina Célia di Ciommo, João Santos Nahum, Yayo Herrero, Rocha and Sobrinho, Farias to the respective categories. The research strict approach in terms of quantitative and qualitative evaluation case report exploratory. As research technique it was realized non directive interviews for data collection through relaxed dialogue and structured quiz. At this stage were indicated the difference between the phases of empirical work developed and its distinct activities in which phase. The thesis is structured in three chapters which are disposed: Chapter One – Historical Context of Female Labour and Dendê Monoculture in Amazônia; Chapter Two – Theoretical Reflections and Methodological Procedures of Political Economy of the Environment to the case report; and Chapter Three – Transformations of Female Labour in Dendê Monoculture: Contradictions between domination and freedom in Tailândia (PA). It was analyzed datas gathered in the study in order of discussions of political ecology and others theoretical references giving rise to female labour transformations in the farms when the Dendê monoculture has arrived in the location.